PERLAWANAN PEREMPUAN DALAM NOVEL ANA NAJUD IBNATU AL-ASYIRAH WA MUTALLAQAH: ANALISIS STRUKTURALISME GENETIK LUCIEN GOLDMANN - Husnaya, Ni'ma Royyin; Halim, Mustabir (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article discusses the representation of patriarchy in the Arab World, especially Yemen. Various forms of violence, oppression, and discrimination against women and children are described in a literary work entitled Ana Najud Ibnatu Al-Asyirah wa Mutallaqah. The novel is also a form of criticism and resistance by the author against the patriarchal culture still strongly embedded in the social environment in which the author lives. The method used in data analysis is the dialectical method, namely the data contained in literary works will be connected to the data contained in the reality of society. This research uses the genetic structuralism approach coined by Lucien Goldmann, who studied literature from aspects of the author's social environment and society to facilitate analysis. The research results show that there is an equivalence (homology) between the structure of the work and the structure of Yemeni society at that time. This equality is found in the worldview of a particular collective subject that the author voices in his work. The views of resistance to patriarchy mentioned above represent the views of oppressed groups of women, especially underage women who experienced forced marriage (shighar) at that time.